Thermal Stability of Glucokinases in Thermoanaerobacter tengcongensis. (24th August 2013) - Qian, Zhong; Zhao, Jingjing; Bai, Xue; Tong, Wei; Chen, Zhen; Wei, Hanfu; Wang, Quanhui; Liu, Siqi
Abstract : In the genome of Thermoanaerobacter tengcongensis, three genes belonging to ROK (Repressor, ORF, and Kinase) family are annotated as glucokinases (GLKs). Using enzyme assays, the three GLKs were identified as ATP-dependent GLK (ATP-GLK), ADP-dependent GLK (ADP-GLK), and N-acetyl-glucosamine/mannosamine kinase (glu/man-NacK). The kinetic properties of the three GLKs such as K m, V max, optimal pH, and temperature were characterized, demonstrating that these enzymes performed the specific functions against varied substrates and under different temperatures. The abundance of ATP-GLK was attenuated when culture temperature was elevated and was almost undetectable at 80°C, whereas the ADP-GLK abundance was insensitive to temperature changes. Using degradation assays, ATP-GLK was found to have significantly faster degradation than ADP-GLK at 80°C. Co-immunoprecipitation results revealed that heat shock protein 60 (HSP60) could interact with ATP-GLK and ADP-GLK at 60 and 75°C, whereas at 80°C, the interaction was only effectively with ADP-GLK but not ATP-GLK. The functions of GLKs in T. tengcongensis are temperature dependent, likely regulated through interactions with HSP60.